Synthesis, characterization and observation of structural diversities in a series of transition metal based furan dicarboxylic acid systems - Sen, Rupam
Six new MOFs have been synthesized by using transition metal ions and 2,5-furandicarboxylic acid, [M(fdc)(bpe)](n) (M = Co(1)/Ni(2)); [M(fdc)(bpee)](n) (M = Co(3)/Ni(4)); [M(fdc)(H2O)(3)](n) (M = Mn(5)/Zn(6)), [where fdc = furan-2,5-dicarboxylic acid, bpe = 1,2-bis(4-pyridyl) ethylene, bpee = 1,2-bis(4-pyridyl)ethane]. All the compounds were characterized by single crystal X-ray analysis and show interesting diversities in their structures. Compounds 1-4 are interesting two-fold interpenetrated 3D frameworks, whereas 5 and 6 have zig-zag chains. Topological analysis on compounds 1-4 revealed that these compounds are uninodal 7-c nets with the Schlafli symbol 3(3).4(13).5(4).6. Compounds 1-4 were subjected for N-2 adsorption study to measure the porosity of the materials. BET measurement shows that compounds 1-4 are microporous having surface areas of 128 m(2) g(-1). The variable temperature magnetic susceptibility measurement reveals the presence of weak interaction in the compounds.